2020
DOI: 10.1111/liv.14350
|View full text |Cite|
|
Sign up to set email alerts
|

A diabetologist’s perspective of non‐alcoholic steatohepatitis (NASH): Knowledge gaps and future directions

Abstract: There is a close link between steatohepatitis (NASH) and Type 2 diabetes (T2DM). Recently, the American Diabetes Association (ADA) recommended screening for NASH and advanced fibrosis in patients with diabetes and hepatic steatosis or elevated plasma alanine aminotransferase (ALT). This is because as many as ~30% to 40% may have NASH and ~10% to 15% advanced fibrosis. The role of hyperglycemia and the natural history of NASH in diabetes remain poorly understood, as well as which diagnostic algorithm or interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 59 publications
1
25
0
4
Order By: Relevance
“…A recent Bayesian network meta-analysis of randomized controlled trials (RCTs) and non-randomized intervention studies of individuals with biopsy-proven NASH showed that pioglitazone and bariatric surgery are the two most effective treatment options for NASH, thereby supporting the notion that weight loss and improvement in hepatic insulin resistance are promising approaches for the treatment of this metabolic liver disease [19]. However, although it has been demonstrated that long-term use of pioglitazone in adults with biopsy-proven NASH has beneficial effects on the histological resolution of NASH, this drug may have some side-effects, such as moderate weight gain, peripheral oedema and risk of distal bone fractures (especially in postmenopausal women) [12,20,21].…”
Section: Introductionmentioning
confidence: 93%
“…A recent Bayesian network meta-analysis of randomized controlled trials (RCTs) and non-randomized intervention studies of individuals with biopsy-proven NASH showed that pioglitazone and bariatric surgery are the two most effective treatment options for NASH, thereby supporting the notion that weight loss and improvement in hepatic insulin resistance are promising approaches for the treatment of this metabolic liver disease [19]. However, although it has been demonstrated that long-term use of pioglitazone in adults with biopsy-proven NASH has beneficial effects on the histological resolution of NASH, this drug may have some side-effects, such as moderate weight gain, peripheral oedema and risk of distal bone fractures (especially in postmenopausal women) [12,20,21].…”
Section: Introductionmentioning
confidence: 93%
“…107 In addition, multimorbidity and polypharmacy are common in patients with type 2 diabetes and NAFLD, highlighting a need for multidisciplinary management to address their complex health-care needs. 108 In secondary care diabetes clinics, the prevalence of advanced fibrosis among patients with NAFLD is 10-20%, [109][110][111][112] which is two to four times higher than in primary care. There is increasing recognition that an assessment of NAFLD and liver fibrosis needs to be incorporated into the routine care of patients with type 2 diabetes.…”
Section: Prevention Evaluation and Management Of Nafld In Primary Care And Diabetes Clinicsmentioning
confidence: 99%
“…There is increasing recognition that an assessment of NAFLD and liver fibrosis needs to be incorporated into the routine care of patients with type 2 diabetes. 109 As a result, the American Diabetes Association now recommends that "Patients with type 2 diabetes and elevated liver enzymes (alanine aminotransferase) or fatty liver on ultrasound should be evaluated for the presence of non-alcoholic steatohepatitis and liver fibrosis." 113 However, alanine aminotransferase mea surements are notoriously inaccurate and are within the normal range in most people with type 2 diabetes and NAFLD; thus with this strategy, many patients with clinically significant liver disease will not be diagnosed.…”
Section: Prevention Evaluation and Management Of Nafld In Primary Care And Diabetes Clinicsmentioning
confidence: 99%
“…En síntesis, los resultados obtenidos con medicacio-nes aprobadas para el uso en pacientes con DM2 abre la interesante posibilidad del tratamiento con "múltiple propósito", en donde se controle con un agente la glucemia y el perfil cardiometabólico, mientras se trata la EHNA. 123,124 Se necesitan estudios a largo plazo para evaluar el impacto en la historia natural y la mortalidad hepática y extrahepática en esta población. Por último, es importante recordar que las guías de la AASLD 4 apoyan el uso de las estatinas en pacientes con EHNA, dado su alto riesgo cardiovascular, aún con transaminasas moderadamente elevadas, pero esto requiere un monitoreo clínico adecuado.…”
Section: Agentes Farmacológicos Para El Tratamiento De La Diabetes Mellitusunclassified